Osteoprotection Through the Deletion of the Transcription Factor Rorβ in Mice. (27th December 2017) - Farr, Joshua N; Weivoda, Megan M; Nicks, Kristy M; Fraser, Daniel G; Negley, Brittany A; Onken, Jennifer L; Thicke, Brianne S; Ruan, Ming; Liu, Hong; Forrest, Douglas; Hawse, John R; Khosla, Sundeep; et al.
ABSTRACT: There is a clinical need to identify new molecular targets for the treatment of osteoporosis, particularly those that simultaneously inhibit bone resorption while stimulating bone formation. We have previously shown in overexpression studies that retinoic acid receptor‐related orphan receptor β (Rorβ) suppresses in vitro osteoblast differentiation. In addition, the expression of Rorβ is markedly increased in bone marrow–derived mesenchymal stromal cells with aging in both mice and humans. Here we establish a critical role for Rorβ in regulating bone metabolism using a combination of in vitro and in vivo studies. We used Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 gene editing to demonstrate that loss of Rorβ in osteoblasts enhances Wnt signaling, specifically through increased recruitment of β‐catenin to T‐cell factor/lymphoid enhancer factor (Tcf/Lef) DNA binding sites in the promoters of the Wnt target genes Tcf7 and Opg . This resulted in increased osteogenic gene expression and suppressed osteoclast formation through increased osteoprotegerin (OPG) secretion in Rorβ‐deficient cells. Consistent with our in vitro data, genetic deletion of Rorβ in both female and male mice resulted in preserved bone mass and microarchitecture with advancing age due to increased bone formation with a concomitant decrease in resorption. The improved skeletal phenotype in the Rorβ –/– mice was also associated with increased bone protein levels of TCF7 and OPG. These data demonstrate that loss of Rorβ has beneficial skeletal effects by increasing bone formation and decreasing bone resorption, at least in part through β‐catenin–dependent activation of the Wnt pathway. Thus, inhibition of Rorβ represents a novel approach to potentially prevent or reverse osteoporosis. © 2017 American Society for Bone and Mineral Research.